2012
DOI: 10.1038/jp.2012.94
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide levels are correlated with birth-weight discordance in monochorionic-diamniotic twins without twin–twin transfusion syndrome

Abstract: Cardiac dysfunction occurs in both larger and smaller co-twins with increasing birth-weight discordances, even in the absence of TTTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…However, controls were either not available or of small sample size [3941]. A further study reported on amniotic fluid and umbilical cord BNP at delivery in monochorionic twin pregnancies, whereby higher levels were present in newborns with weight discordance >20% or myocardial dysfunction [42]. …”
Section: Discussionmentioning
confidence: 99%
“…However, controls were either not available or of small sample size [3941]. A further study reported on amniotic fluid and umbilical cord BNP at delivery in monochorionic twin pregnancies, whereby higher levels were present in newborns with weight discordance >20% or myocardial dysfunction [42]. …”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, it is reasonable that the increased levels of NT-proBNP in larger twins of sIUGR could be due to volume overload as a similar mechanism as in recipients of TTTS. A possible reason for increased BNP levels in smaller twins of sIUGR may be pressure overload induced by renin-angiotensin system activation, hypoxemia resulting from hypovolemia, facilitating BNP release 15,27 and intrauterine growth retardation, which is associated with increased cardiac workload. 31 A limitation of this study is the relatively small number of sIUGR patients, as this was a retrospective observational study at a single center.…”
Section: Larger Twinmentioning
confidence: 98%
“…Moreover, BNP levels in umbilical cord blood and amniotic fluid are positively correlated with birth-weight discordance in the larger twin, as well as the smaller twin, among MD twins in the absence of a diagnosis of TTTS. 15 However, no reports have assessed the cardiac workload in sIUGR by measuring serum NT-proBNP levels at birth. Therefore, the purpose of this study was to compare serum NT-proBNP levels at birth in MD twins with sIUGR with those without sIUGR.…”
Section: Introductionmentioning
confidence: 99%
“…Moriichi et al investigated AF BNP in monochorionic diamniotic (MD) twin pregnancies without TTTS at birth and found elevated AF BNP levels in patients with cardiac dysfunction monitored by postnatal echocardiography and in newborns with >20% weight diference. 17 However, there is no published study investigating the correlation between AF NP levels and HF in fetuses with CHD or arrhythmia.…”
mentioning
confidence: 99%